Pemberian Pupuk Trichokompos Pada Tanah Ultisol Terhadap Pertumbuhan Bibit Kakao ( Theobroma cacao L.) Di Polybag - Rosita, Winda; Nasamsir, Nasamsir; Nengsih, Yulistiati (Universitas Batanghari, 2025)
Cocoa (Theobroma cacao L.) is one of Indonesia's leading plantation commodities that has the potential to be processed into chocolate products. Cocoa contains natural antioxidants and has considerable prospects in improving the welfare of the community. The research was conducted from May to August 2024 in Andilan Hamlet, Kasang Kota Karang Village, Kumpeh Ulu District, Muaro Jambi Regency. The design used in this study was a one-factor completely randomised design (CRD). The treatment design used is the dose of trichocompost consisting of 4 dose levels as follows: t0 = Without trichocompost (control), t1 = 50 g trichocompost fertiliser, t2= 75 g trichocompost fertiliser, and t3 = 100 g trichocompost fertiliser. The study consisted of 3 replications so that 12 experimental plots were obtained. The number of plants in each plot was 4 plants, 3 plants were taken as samples, so the total number of plants was 4 x 3 x 4 = 48 seedlings. The results of analysis of variance showed that the application of trichocompost fertiliser had a significant effect on plant height, and crown dry weight, but had no significant effect on stem diameter, root crown ratio, and root dry weight. The application of trichocompost fertiliser up to a dose of 50 g/polybag generally showed no difference in the growth of cocoa seedlings aged 12 weeks after planting.